1998
DOI: 10.1016/s0741-5214(98)70101-6
|View full text |Cite
|
Sign up to set email alerts
|

“Marsupial cava” and ruptured abdominal aortic aneurysm

Abstract: A patient with a ruptured abdominal aortic aneurysm underwent an emergency operation. A rare anomaly of inferior vena cava, known as "marsupial cava," was found. The iliac vein confluence crossed anteriorly (rather then posteriorly) the right common iliac artery. Even though the patient had undergone a computed tomography scan, this rare anomaly had not been detected and therefore was unexpected by the surgeon. The aim of this report is to describe the technical details required to perform the aortic reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, Rocha concluded that marsupial IVC could not be as rare as previously thought because authors observed four cases of IVC during a period of two years [41]. Case reports associated with vascular surgery have described most cases of this anomaly [38,42,43]. Generally, the anomaly is asymptotic and unrelated to abnormal venous drainage from the lower venous parts of the body [38].…”
Section: Marsupial Ivc Prevalence and Surgical Anatomymentioning
confidence: 97%
“…However, Rocha concluded that marsupial IVC could not be as rare as previously thought because authors observed four cases of IVC during a period of two years [41]. Case reports associated with vascular surgery have described most cases of this anomaly [38,42,43]. Generally, the anomaly is asymptotic and unrelated to abnormal venous drainage from the lower venous parts of the body [38].…”
Section: Marsupial Ivc Prevalence and Surgical Anatomymentioning
confidence: 97%
“…4A) (Shindo et al, 1999). Because such an anterior position of IVC is typical in most marsupials, as stated by McClure and Huntington in 1929, compared with the posterior position present in placental mammalians, it is used the term "marsupial cava" (Schiavetta et al, 1998).…”
Section: Marsupial Cava or Preaortic Venous Confluencementioning
confidence: 99%
“…With a careful blunt dissection of the right common iliac artery bifurcation, it is possible to gain distal control without mobilizing the caval confluence, which results strictly adherent to aorta. On the contrary, this anomaly is very troublesome if the distal aorta and right common iliac artery are approached retroperitoneally from the patient's right side (Schiavetta et al, 1998). During emergency surgery, the priority of gaining quick control of the aorta and the iliac arteries through the retroperitoneal hematoma may lead to injury to major venous structures, excessive hemorrhage, and subsequent death.…”
Section: Marsupial Cava or Preaortic Venous Confluencementioning
confidence: 99%
“…With a careful blunt dissection of the right common iliac artery bifurcation, it is possible to gain distal control without mobilizing the caval confluence, which results strictly adherent to aorta. On the contrary, this anomaly is very troublesome if the distal aorta and right common iliac artery are approached retroperitoneally from the patient's right side (Schiavetta et al, 1998).…”
Section: Marsupial Cava or Preaortic Venous Confluencementioning
confidence: 99%